Computer sciences student competency system (CSSCS) for data communication and networking (CS225) - Jaafar, Syuhada (2013)
This project of Computer Sciences Student Competency System (CSSCS) has the objectives to identify the technical skills needed by industry for Data Communication and Networking (CS225) graduates based on the job opportunities, to identify the user requirements for student competency system, to design a system that can map the industry needs and university supplies and lastly to develop a system that can map the industry needs and university supplies. The scope of this project is that it will be concentrated on the Computer Sciences program in Faculty of Computer and Mathematical Sciences in UiTM Shah Alam. The methodology that will be used in the system is Rapid Application Development (RAD) methodology because it is the methodology that appropriate with the project. The analysis and findings of the project including the literature review analysis based on the topics that relate to the project, the interview to determine the user requirements of the client for the system and also the questionnaire about the development of the project. This project is developing to ease the evaluation of the student by the evaluator and supervisor.